Effect of Oyster Meat Preload on Postmeal Glycemic Control in Healthy Young Adults. (17th August 2020) - Lin, Shuting; Hao, Gengxin; Lai, Dong; Tian, Yan; Long, Min; Lai, Fei; Xiong, Yongmei; Ji, Changfu; Zang, Yuan
Abstract: Objective: Evidence suggests that food preload improves postmeal glycemic profiles, but the effects of marine food are poorly understood. Our study aims to verify the regulating effects of premeal oyster meat (OM) on postprandial blood glucose. Method: Edible parts of the flesh of oyster were prepared for a randomized crossover experiment. After overnight fasting, 20 healthy young men consumed 300 mL of preload drinks with 0 g/kg body weight (BW) (control), 0.1 g/kg BW, and 0.2 g/kg BW. Peripheral blood concentrations of glucose and gastrointestinal hormones were measured before preloading at baseline (0 minutes) and at intervals after the preload and after a preset rice meal. The nutrient composition of OM was analyzed. Results: Compared with other doses, 0.2 g/kg BW OM preload induced higher plasma premeal insulin ( p  < 0.05), C-peptide ( p  < 0.05), and glucagon-like peptide-1 (GLP-1; p  < 0.05) without altering the glucose concentrations during premeal times. By contrast, 0.2 g/kg BW OM induced less secretion of glucose ( p  < 0.05) and gastric inhibitory peptide (GIP; p  < 0.05), but higher secretion of GLP-1 ( p  < 0.05) than 0.1 g/kg BW of OM after a meal. During the entire experiment (0–170 minutes), OM reduced the blood glucose ( p  < 0.05) and GIP ( p  < 0.05), but increased GLP-1 ( p  < 0.05). OM was rich in protein (78.4%) and low in fat (6%). Glutamic acid, aspartic acids, glycine, and taurine are the amino acids with high content found in OM. Conclusions: OM preload reduces postmeal glycemia in healthy young people with associated changes in gastrointestinal hormone responses. This effect may be attributed to the rich contents of protein and amino acids of OM.